2015
DOI: 10.1089/ars.2013.5748
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin II Negatively Regulates Lipopolysaccharide-Induced Osteoclast Formation and Bone LossviaJNK and STAT3

Abstract: Aims: Lipopolysaccharide (LPS) is considered a prominent pathogenic factor in inflammatory bone diseases. LPS challenge contributes to the production of reactive oxygen species (ROS) in diverse inflammatory diseases. However, its mechanism remains to be clarified in bone. Thus, we investigated the critical mechanism of ROS in LPS-induced osteoclastogenesis and bone loss. Results: Antioxidant prevented LPS-induced osteoclast formation via inhibition of nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…Moreover, either inhibition of JNK1 activity by a specific inhibitor or knockdown of JNK1 by RNA interference significantly decreased osteoclast formation (9). Similar findings were also reported by other investigations (13)(14)(15)(16). Consistently, the JNK kinase assay showed that JNK1 was specifically activated by RANKL (12).…”
supporting
confidence: 83%
“…Moreover, either inhibition of JNK1 activity by a specific inhibitor or knockdown of JNK1 by RNA interference significantly decreased osteoclast formation (9). Similar findings were also reported by other investigations (13)(14)(15)(16). Consistently, the JNK kinase assay showed that JNK1 was specifically activated by RANKL (12).…”
supporting
confidence: 83%
“…40,41 Prx2 gene expression was markedly upregulated in SCD mice compared with healthy controls (supplemental Figure 1C), whereas Catalase expression was similar in both mouse strains (data not shown).…”
Section: Acid As Multimodal Therapy For Sbd 2321mentioning
confidence: 89%
“…SAA1, a major acute phase protein, stimulates MMP9 production for bone resorption (Paret, Schon, Szponar & Kovacs, 2010). In contrast, peroxiredoxin 2 (PRDX2), a member of the antioxidant enzyme family, is protective against oxidative damage during osteoclastogenesis (Park et al., 2015). …”
Section: Discussionmentioning
confidence: 99%